2009
DOI: 10.1063/1.3211957
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependent dielectric and mechanical behavior of elastomers for actuator applications

Abstract: The low frequency mechanical and dielectric behavior of three different elastomers has been investigated by dynamic mechanical analysis and dielectric spectroscopy, with the aim of accounting for the frequency dependence of the characteristics of the corresponding dielectric elastomer actuators. Satisfactory agreement was obtained between the dynamic response of the actuators and a simple model based on the experimental data for the elastomers, assuming that the relatively large prestrains employed in the actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 17 publications
6
85
1
Order By: Relevance
“…With 1 kHz of useable bandwidth for full-amplitude signals, the silicone-based tuneable lens presented here is more than 3 orders of magnitude faster than devices made with acrylic elastomer. constantly and rapidly decreasing strain amplitude for frequencies ranging from 10 -3 Hz to 1 Hz, [18] an observation also reported by Keplinger et al between 0.04…”
Section: Frequency Responsesupporting
confidence: 67%
See 1 more Smart Citation
“…With 1 kHz of useable bandwidth for full-amplitude signals, the silicone-based tuneable lens presented here is more than 3 orders of magnitude faster than devices made with acrylic elastomer. constantly and rapidly decreasing strain amplitude for frequencies ranging from 10 -3 Hz to 1 Hz, [18] an observation also reported by Keplinger et al between 0.04…”
Section: Frequency Responsesupporting
confidence: 67%
“…[19] The acrylic elastomer VHB has a very high mechanical loss tangent, increasing from 0.3 to almost 1 in the 1 mHz to 100 Hz frequency range. [18] Molberg et al observed that although at very low frequencies acrylic elastomerbased devices lead to larger strains compared to silicone devices, the strain of their silicone actuators was larger than acrylic elastomer (VHB) actuators for frequencies above 0.1Hz.…”
Section: Frequency Responsementioning
confidence: 99%
“…But using a PDMS stamp to pattern carbon powders on a PDMS membrane is more difficult as the stamp and film have the same surface energies. Silicone films are increasingly preferred to acrylic elastomer films since they have negligible viscoelastic properties and stable dynamic behavior, and longer lifetime [10]. Pimpin et al have shown buckling mode microactuators using patterned concentric circle metal electrodes on silicone elastomers [11], but these electrodes still have a significant impact on the stiffness of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the actuation strain of VHB decreases rapidly with frequency because of its high viscous losses, and at driving frequencies above 1 Hz, the actuation strain of silicone-based actuators exceeds that of VHB-based actuators. 9 Consequently, except for demonstrating giant actuation strain at low frequencies, silicone-based actuators exhibit better performance, especially regarding stability in time, and we therefore systematically use silicone elastomers for our DEAs.…”
Section: Elastomer Membranesmentioning
confidence: 99%